Linseed Oil-Based Oleogel Vehicles for Hydrophobic Drug Delivery-Physicochemical and Applicative Properties - Sonia Kudłacik-Kramarczyk; Anna Drabczyk; Alicja Przybyłowicz; Marcel Krzan (MDPI AG, 2024)
In this study, a methodology for synthesizing oleogels based on linseed oil and emulsifiers, such as beeswax and Tween 20 and Tween 80, was developed. Linseed oil served as the main oil phase, while beeswax acted as a gelling and emulsifying agent. Tween compounds are non-ionic surfactants composed of hydrophobic and hydrophilic parts, allowing for the formation of a stable system with promising properties. Surface wetting analysis of the obtained oleogels, FT-IR spectroscopy, and determination of relative and absolute humidity over time, as well as optical microscope analysis and rheological analysis of the obtained oleogels, were conducted as part of the research. The results indicate that increasing the amount of Tween 20 decreases the hydrophilicity of the oleogel, while Tween 80 exhibits the opposite effect. Surface energy analysis suggests that a higher content of Tween 20 may lead to a reduction in the surface energy of the oleogels, which may indicate greater material stability. Changes in relative humidity and FT-IR spectral analysis confirm the influence of emulsifiers on the presence of characteristic functional groups in the structure of the oleogels. Additionally, microscopic analysis suggests that an emulsifier with a longer hydrophobic tail leads to a denser material structure.